Multi-site project management: A domain for crafting an ontology system methodology and system architecture - Cheah, Chan; Chang, Elizabeth (Idea Group Inc, 2005)
Multi-site project management (the domain in analysis) is a growing practice with little documented research. It has many knowledge-based issues resulting from the dispersion of people, systems and resources. An ontology knowledge system is proposed as one solution that would help resolve these issues. This paper suggests a 3-phased approach ? conceptualising a system design framework, designing the underpinning development methodology, and developing an ontology knowledge system solution for supporting multi-site project management.